2023
DOI: 10.1093/genetics/iyad050
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of recapitulating polygenic effects in natural populations: replication of genetic effects on wing shape in artificially selected and wild-caught populations of Drosophila melanogaster

Abstract: Identifying the genetic architecture of complex traits is important to many geneticists, including those interested in human disease, plant and animal breeding, and evolutionary genetics. Advances in sequencing technology and statistical methods for genome-wide association studies (GWAS) have allowed for the identification of more variants with smaller effect sizes, however, many of these identified polymorphisms fail to be replicated in subsequent studies. In addition to sampling variation, this failure to re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Alternatively, it is possible that these effect vectors do not estimate directions of effects well, and further titrating the strength of knockdowns may help to obtain better estimates. It is also possible that the RNAi knockdown does not correlate with the segregating allelic effect of the candidate genes, although previous studies have demonstrated correlation between segregating polymorphisms and genetic knockdown effects for wing shape (Pelletier et al, 2023; Pitchers et al, 2019). Quantitative complementation mapping experiments identified two regions that may be related to shape change in the same direction as the altitudinal effect vector (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, it is possible that these effect vectors do not estimate directions of effects well, and further titrating the strength of knockdowns may help to obtain better estimates. It is also possible that the RNAi knockdown does not correlate with the segregating allelic effect of the candidate genes, although previous studies have demonstrated correlation between segregating polymorphisms and genetic knockdown effects for wing shape (Pelletier et al, 2023; Pitchers et al, 2019). Quantitative complementation mapping experiments identified two regions that may be related to shape change in the same direction as the altitudinal effect vector (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Hippo developmental network is best known for its role in regulation of organ size, including the size of Drosophila wings. Variants in genes in the hippo signaling pathway influence wing shape variation, with correlated phenotypic effects (Pelletier et al, 2023; Pitchers et al, 2019). Interestingly, allele frequency changes across multiple hippo signaling loci following artificial selection for wing shape changes did not result in substantial wing size change (Pelletier et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This redundancy can explain why genetic changes underlying parallel evolution often fail to be replicated (e.g., ref. 41 ), since multiple changes at the genetic level can explain the same phenotypic adaptations.…”
Section: Discussionmentioning
confidence: 99%